MicroRNA-Based Diagnosis and Therapeutics for Vascular Cognitive Impairment and Dementia - Zhai, Weijie; Zhao, Meng; Zhang, Guimei; Wang, Zicheng; Wei, Chunxiao; Sun, Li (Frontiers in Neurology, 2022)
Vascular cognitive impairment and dementia (VCID) is a neurodegenerative disease that is recognized as the second leading cause of dementia after Alzheimer's disease (AD). The underlying pathological mechanism of VCID include crebromicrovascular dysfunction, blood-brain barrier (BBB) disruption, neuroinflammation, capillary rarefaction, and microhemorrhages, etc. Despite the high incidence of VCID, no effective therapies are currently available for preventing or delaying its progression. Recently, pathophysiological microRNAs (miRNAs) in VCID have shown promise as novel diagnostic biomarkers and therapeutic targets. Studies have revealed that miRNAs can regulate the function of the BBB, affect apoptosis and oxidative stress (OS) in the central nervous system, and modulate neuroinflammation and neurodifferentiation. Thus, this review summarizes recent findings on VCID and miRNAs, focusing on their correlation and contribution to the development of VCID pathology.